c.1 - Rao, V. M. (ed. ) (New Delhi, 1989)
Recent years have witnessed a substantial expansion in the programmes for the poor. With each five-year plan document, the strategy towards the poor-atleast in its objectives and targets-has been becoming more and more ambitious. This volume presents in depth and detailed investigations of selected programmes for the poor. The studies cover all the three major categories of the programmes, namely, (a) relief and support measures, (b) programmes for creating new economic opportunities for the poor and (c) programmes for reforming social structure and relationships. In the place of a purely statistical approach to evaluation of the impact of the programmes, the perspective adopted in this volume is that of a social science observer looking at the programmes against the background of broader rural change with a view to assessing the present and potential usefulness of the programmes to the poor in their struggles to join the mainstream. The volume would be of particular use and interest to researchers, policy makers and more pertinently, to the growing number of graduate and post-graduate students taking up course in rural development.
Keywords: Poverty